Selective collection in the municipality of Narandiba – São Paulo – Brazil - Branco, Cláudio Domingues; Rizk, Maria Cristina; Araújo, Renata Ribeiro de (National Journal of City Management, 2025)
Objective – The present work aimed to evaluate selective collection in the municipality of Narandiba – São Paulo, from its implementation to the present day, through the analysis of actions developed in the municipality such as: logistics, environmental education, infrastructure and public policies.Methodology – The study was based on monitoring door-to-door selective collection in several neighborhoods in the urban area of the municipality, as well as monitoring the activities developed by the Association of Nature Protectors (APRONAT), including the collection, sorting, storage and marketing of recyclable materials. Administrative documents related to the management of recyclable materials were also analyzed. Based on the analysis of primary data collected in the field and secondary data collected, actions were proposed to improve selective collection in the municipality.Originality/Relevance – The study deals with an applied research on selective collection in a small municipality, a perspective little explored in the literature on urban solid waste management. The relevance of the work consists in the analysis of logistical, educational, financial, structural and political aspects and their influence on the performance of selective collection in small municipalities.Results – In 2015, 43 tons of recyclable materials collected by APRONAT were sold, and in 2023, 138 tons were sold, indicating an increase in the collection, sorting and marketing capacity of recyclable materials. Environmental education actions developed by schools and by APRONAT itself improved the correct disposal of waste, together with financial support for collectors and other incentives from the government, which helped improve selective collection and APRONAT's operational process. However, there is still a need to improve the operational infrastructure of selective collection, training and education of recyclable material collectors and support from the population in the separation and disposal of recyclable materials.Theoretical/Methodological Contributions – The theoretical/methodological contributions highlight the importance of the circular economy and recycling, highlighting the need for public policies adapted to local realities. The methodology used an approach that integrated quantitative and qualitative analyses for the integrated management of solid waste.Social and Environmental Contributions – The study generated social and environmental contributions. From a social perspective, it highlighted the importance of social inclusion through the promotion of associations of recyclable material collectors and the generation of jobs and income in the recycling chain. From an environmental perspective, it highlighted the importance of selective collection to reduce negative impacts on the environment, promoting more efficient use of natural resources and reducing the volume of waste sent to landfills and irregular disposal of solid waste.
Keywords: Selective collection; Recyclable material collectors; Solid Waste Management